2019
DOI: 10.1186/s13071-019-3857-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of Echinococcus spp. in yaks and sheep in the Tibet Autonomous Region of China based on mitochondrial DNA

Abstract: BackgroundCystic echinococcosis (CE) in humans and livestock is caused by Echinococcus granulosus (sensu lato). In China where CE is endemic, a number of studies have shown that Echinococcus granulosus (sensu stricto) is majorly responsible for CE. However, E. canadensis (G6) which is the second leading cause of CE is now being detected in most parts of the country. In this study, the species diversity and genetic variation of Echinococcus granulosus (s.l.) in four counties in Tibet Autonomous Region of China … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
5
8
0
Order By: Relevance
“…Although the prevalence of echinococcosis was explored [ 28 ], the causative agents of human infection have not yet been fully understood in TAR. Previous molecular studies on the Tibetan Plateau often included samples from animals; even when samples from humans were involved, they were mainly patients from Qinghai or Sichuan Provinces, with few patients from TAR; moreover, previous studies were using short fragments of the mtDNA with limited phylogenetic resolution [ 5 , 9 , 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the prevalence of echinococcosis was explored [ 28 ], the causative agents of human infection have not yet been fully understood in TAR. Previous molecular studies on the Tibetan Plateau often included samples from animals; even when samples from humans were involved, they were mainly patients from Qinghai or Sichuan Provinces, with few patients from TAR; moreover, previous studies were using short fragments of the mtDNA with limited phylogenetic resolution [ 5 , 9 , 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there was a prevalence study in TAR using ultrasound diagnostics, molecular markers were seldom used to identify the Echinococcus species and genotypes infecting the echinococcosis patients in TAR. Previous molecular epidemiological studies in this region often included animal samples with very few samples from humans; even when samples from patients were involved, they were mainly patients from Qinghai or Sichuan Provinces, but rarely patients from TAR; besides, previous studies were using short fragments of the mtDNA such as cox 1, a fragment of cox 1, nad 1, and atp 6 [ 5 , 9 , 25 27 ], which could not confidently allocate the samples into specific genotypes and could only generate networks with lower resolution; therefore, the exact Echinococcus species and genotypes infecting humans in TAR remain unknown. The accurate allocation of the samples into different species and genotypes is the prerequisite for the exploration of the epidemiology, pathology, and infectivity to humans of the different species and genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other species of Echinococcus present on the Tibetan Plateau, for example, E. multilocularis, a sister species to E. shiquicus which also shares similar host characteristics, demonstrates a relatively lower mitochondrial polymorphism (Nakao et al, 2010;Li et al, 2018), although this species has a more generalistic host requirement with zoonotic potentials. Similarly, on the plateau low mitochondrial polymorphism is also true for E. granulosus sensu stricto, a widespread and geographically expanding species (Nakao et al, 2010;Ohiolei et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Whereas the relationship between human and cattle represented with identical haplotype (H11) , that means the most infection of human with hydatid cysts come from dogs that ate hydatid cysts from cattle. Through the study it was found that the two isolates number (1,8) these isolate genetically similar to isolates from sheep in the city (Saga in Japan), isolates number (2,3,4,5,6) genetically similar to isolates from sheep and yak in the city (Zhongba in China) (16) . The isolates number(7) genetically similar to isolates from human in the China country (17) .…”
Section: Picture(1): Agarose Gel Electrophoresis Image That Showed the Pcr Product Analysis Of Mitochondrial Nad(1) Gene In E Granulosus mentioning
confidence: 91%